PENGARUH STRATEGI DIRECTED LISTENING THINKING ACTIVITY (DLTA) BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENYIMAK DONGENG - Nurani, Riga Zahara (2017)
In listening lesson, students should understand the intrinsic elements of fairy tale that includes a character, setting, theme, plot, and massage. Listening lesson in schools usually do not stimulate students to think critically, because the teacher just read a fairy tales in front of the class and student only listen. Therefore, it is necessary learning strategy capable of stimulating students to think critically, on which strategy is Directed Listening Thinking Activity (DLTA). In addition, the use of audio visual is also required in order to make learning more meaningful. This research is conducted in class V SDN 6 Singaparna. On experiment class applied strategy of Directed Listening Thinking Activity (DLTA) assisted by audio visual, whereas in the control class is applied direct learning. Average listening ability of fairy tale on experiment class before being given preferential treatment is 67,20 and after increased is 84,53. While the average listening ability of fairy tale on control class before being given treatment is 67,26 and after being given the treatment is 77,55. Based on the results of a test using SPSS t-22 retrieved tcount = 4,445 and at α = 0.05, df = 59 and test (1-tailed) obtained tcritical = 1,671. Because tcount > tcritical, then H0 is rejected. In conclusion, there is a different score listening ability to fairy tale on experimental's class and control class. Thus, the strategy of Directed Listening Thinking Activity (DLTA) make an effect to listening ability of fairy tales. Dalam pembelajaran menyimak, siswa harus memahami unsur-unsur intrinsik dongeng yang meliputi tokoh, latar, tema, alur, dan amanat. Pembelajaran menyimak di sekolah kurang bisa mengajak siswa untuk berpikir, karena guru hanya membaca dongeng di depan kelas sementara siswa mendengarkan. Oleh karena itu, diperlukan strategi pembelajaran yang mampu merangsang siswa untuk berpikir, salah satunya adalah strategi Directed Listening Thinking Activity (DLTA). Penggunaan media audio visual juga diperlukan agar pembelajaran lebih bermakna. Penelitian ini dilakukan di kelas V SDN 6 Singaparna Kabupaten Tasikmalaya. Pada kelas eksperimen diterapkan strategi Directed Listening Thinking Activity (DLTA) berbantuan media audio visual, sedangkan pada kelas kontrol diterapkan metode ceramah. Rata-rata kemampuan menyimak dongeng kelas eksperimen sebelum diberi perlakuan adalah 67,20 dan setelah diberi perlakuan meningkat menjadi 84,53. Rata-rata kemampuan menyimak dongeng kelas kontrol sebelum diberi perlakuan adalah 67,26 dan setelah diberi perlakuan menjadi 77,55. Berdasarkan hasil Uji-t menggunakan SPSS 22 diperoleh thitung = 4,445 dan pada α = 0,05, df = 59 dan uji (1-tailed) maka diperoleh tkritis = 1,671. Karena thitung > tkritis, maka H0 ditolak. Kesimpulannya, terdapat perbedaan skor kemampuan menyimak dongeng kelas eksperimen dan kelas kontrol. Dengan demikian, strategi Directed Listening Thinking Activity (DLTA) berpengaruh terhadap kemampuan menyimak dongeng siswa. Kata kunci: Kemampuan menyimak dongeng, Strategi Directed Listening Thinking Activity (DLTA), Unsur-unsur intrinsik